Are Microcredit Interest Rates Excessive? - Rosenberg, Richard; Gonzalez, Adrian; Narain, Sushma (World Bank, Washington, DC, 2012)
Over the past two decades, institutions that make micro loans to low-income borrowers in developing and transition economies have focused increasingly on making their operations financially sustainable by charging interest rates that are high enough to cover all their costs. They argue that doing so will best ensure the permanence and expansion of the services they provide. Sustainable (i.e., profitable) microfinance providers can continue to serve their clients without needing ongoing infusions of subsidies, and can fund exponential growth of services for new clients by tapping commercial sources, including deposits from the public.